Structure–activity correlations of variant forms of the B pentamer of Escherichia coli type II heat-labile enterotoxin LT-IIb with Toll-like receptor 2 binding - Cody, Vivian (International Union of Crystallography, 2012)
The pentameric B subunit of the type II heat-labile enterotoxin of Escherichia coli (LT-IIb-B(5)) is a potent signaling molecule capable of modulating innate immune responses. It has previously been shown that LT-IIb-B(5), but not the LT-IIb-B(5) Ser74Asp variant [LT-IIb-B(5)(S74D)], activates Toll-like receptor (TLR2) signaling in macrophages. Consistent with this, the LT-IIb-B(5)(S74D) variant failed to bind TLR2, in contrast to LT-IIb-B(5) and the LT-IIb-B(5) Thr13Ile [LT-IIb-B(5)(T13I)] and LT-IIb-B(5) Ser74Ala [LT-IIb-B(5)(S74A)] variants, which displayed the highest binding activity to TLR2. Crystal structures of the Ser74Asp, Ser74Ala and Thr13Ile variants of LT-IIb-B(5) have been determined to 1.90, 1.40 and 1.90 Å resolution, respectively. The structural data for the Ser74Asp variant reveal that the carboxylate side chain points into the pore, thereby reducing the pore size compared with that of the wild-type or the Ser74Ala variant B pentamer. On the basis of these crystallographic data, the reduced TLR2-binding affinity of the LT-IIb-B(5)(S74D) variant may be the result of the pore of the pentamer being closed. On the other hand, the explanation for the enhanced TLR2-binding activity of the LT-IIb-B(5)(S74A) variant is more complex as its activity is greater than that of the wild-type B pentamer, which also has an open pore as the Ser74 side chain points away from the pore opening. Data for the LT-IIb-B(5)(T13I) variant show that four of the five variant side chains point to the outside surface of the pentamer and one residue points inside. These data are consistent with the lack of binding of the LT-IIb-B(5)(T13I) variant to GD1a ganglioside.